Feed the Children - Laurens Cherchye; Pierre-André Chiappori; Bram De Rock; Charlotte Ringdal; Frederic Vermeulen (Institute of Labor Economics (IZA), 2021)
To understand the household decision-making process regarding food expenditures for children in poor households in Nairobi, we conduct an experiment with 424 married couples. In the experiment, the spouses (individually and jointly) allocated money between themselves and nutritious meals for one of their children. First, we find strong empirical support for individual rationality and cooperative behavior. Second, our results suggest that women do not have stronger preferences for children's meals than men. Third, the spouses' respective bargaining positions derived from consumption patterns strongly correlate with more traditional indicators. Finally, we document significant heterogeneity both between individuals and intra-household decision processes.
Keywords: C14; D13; C91; C92; 330; collective model; intra-household allocation; experiment; Kenya; children